Examining the Bordered Heterocosm of The Elder Scrolls V: Skyrim: Spaces, Boundaries, Transgression and Sociocultural Significance - Bispo, Jéssica Iolanda Costa (Loading, 2025)
This article explores the video game The Elder Scrolls V: Skyrim, examining its bordered heterocosm by carefully looking at how in-game cities are constructed and how certain spaces within them can be regarded as heterotopias, thus denouncing and exposing sociocultural inequalities, which are enforced and maintained through numerous physical and abstract boundaries. Then, the role of the Dragonborn will be taken into consideration, so as to understand how this character, as the video game’s protagonist, transgresses these same boundaries without being subjected to the repercussions faced by the majority of non-player characters. As such, the Dragonborn is capable of subverting the very core dynamics of transgression, while holding a privileged social status within the video game’s rich and deeply fragmented world.